2022
DOI: 10.1186/s12888-022-03885-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of postnatal depression in the slums Nairobi, Kenya: a cross-sectional study

Abstract: Background Postnatal depression (PND) is a universal mental health problem that prevents mothers’ optimal existence and mothering. Although research has shown high PND prevalence rates in Africa, including Kenya, little research has been conducted to determine the contributing factors, especially in low-resource communities. Objective This study aimed to investigate the PND risk factors among mothers attending Lang’ata and Riruta Maternal and Child… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The screening tools used in Northern Ghana, Kenya and Brazil were different from the screening tools used in the current study. Centre for Epidemiological Studies Depression Screening Scale (CES-D), Beck's Depression Inventory (BDI) and EPDS were used in Northern Ghana, Kenya and Brazil respectively, Whereas the current study used PHQ-9 which has more sensitivity compared to tools employed in previous studies in Africa and Brazil (49)(50)(51) In this regard, the use of PHQ-9 may overestimate the prevalence of maternal depression among mothers of children with undernutrition. The other plausible explanation for the discrepancy in the prevalence rate between our current study and the previous study in Brazil may be attributable to the type of research design employed, speci cally the cohort used in Brazil (51).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The screening tools used in Northern Ghana, Kenya and Brazil were different from the screening tools used in the current study. Centre for Epidemiological Studies Depression Screening Scale (CES-D), Beck's Depression Inventory (BDI) and EPDS were used in Northern Ghana, Kenya and Brazil respectively, Whereas the current study used PHQ-9 which has more sensitivity compared to tools employed in previous studies in Africa and Brazil (49)(50)(51) In this regard, the use of PHQ-9 may overestimate the prevalence of maternal depression among mothers of children with undernutrition. The other plausible explanation for the discrepancy in the prevalence rate between our current study and the previous study in Brazil may be attributable to the type of research design employed, speci cally the cohort used in Brazil (51).…”
Section: Discussionmentioning
confidence: 87%
“…The current prevalence nding of maternal depression was also higher in studies done outside Ethiopia in a study among mothers of children with malnutrition that involved a comparative study between African countries; speci cally Northern Ghana, Kenya for which the prevalence rate was reported at 27.8% and 27.1% respectively (49,50), Similarly in the current study the prevalence of maternal depression was also higher than a study done at Brazil which reported 17.9% (51). The possible reason for those variations may be due to differences in the socioeconomic status of participants, maternal educational status, screening tools and cut-off points, study setting and availability of health facilities between those countries.…”
Section: Discussionmentioning
confidence: 89%
“…The impact of intimate partner violence aligns with the importance of good partner support. Additionally, previous mental health issues, which may be triggered or exacerbated by extreme negative events, are known to be associated with PND, emphasizing the significance of individual's personal history in assessing the risk of PND (18,35). It is noteworthy that many of the economic and social factors typically associated with PND did not emerge as significant predictors in the multivariate or bivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Women in Rural Ethiopia received less social support or even help in family and house work (Abadiga, 2019). According to Kariuki et al (2022), low income for women in the African countries affects negatively their emotional state. This was because mothers may not concentrate on the current state but remain in deep thoughts of what is ahead of them in terms of their inability to pay hospital fees or even afford a meal for herself, baby and entire family (Kariuki et al, 2022).…”
Section: Introductionmentioning
confidence: 99%